2007
DOI: 10.1080/10286020500480522
|View full text |Cite
|
Sign up to set email alerts
|

9, 10-Dihydrophenanthrene derivatives fromPholidotayunnanensisand scavenging activity on DPPH free radical

Abstract: Three new 9,10-dihydrophenanthrene derivatives named phoyunnanins A-C, together with six known 9,10-dihydrophenanthrene constituents, 4,4',7,7'-tetrahydroxy-2,2'-dimethoxy-9,9',10,10'-tetrahydro-1,1'-biphenanthrene (4), lusianthridin (5), eulophiol (6), 2,4,7-trihydroxy-9,10-dihydrophenanthrene (7) and imbricatin (8), were isolated from the 60% ethanolic extract of air-dried whole plant of Pholidota yunnanensis Rolfe. The structures of phoyunnanins A-C were established as 6-[2'-(3',3''-dihydroxy-5'-methoxybibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 5 publications
5
41
0
Order By: Relevance
“…Each stilbenoid isolated from Vanda coerulea stems was already described for its radical scavenging properties mostly concerning DPPH neutralization [33][35]. Zhang X et al had evaluated radical scavenging properties of gigantol ( 3 ) using the DPPH (IC 50 56.4 µM) and ORAC assays [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each stilbenoid isolated from Vanda coerulea stems was already described for its radical scavenging properties mostly concerning DPPH neutralization [33][35]. Zhang X et al had evaluated radical scavenging properties of gigantol ( 3 ) using the DPPH (IC 50 56.4 µM) and ORAC assays [33].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang X et al had evaluated radical scavenging properties of gigantol ( 3 ) using the DPPH (IC 50 56.4 µM) and ORAC assays [33]. Wang J et al and Guo XY et al indicated that coelonin ( 5 ) and imbricatin ( 1 ) neutralized DPPH radical with IC 50 of 16.7 and 8.8 µM, respectively [34], [35]. Finally, the global antioxidant activities of flavidin ( 4 ) were evaluated using different antioxidant assays, including DPPH and hydrogen peroxide neutralization (without IC 50 calculation) [36].…”
Section: Resultsmentioning
confidence: 99%
“…In the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay, only phoyunnanin C (5) showed cytotoxic effects at the test concentrations. Interestingly, previous studies showed that diverse stilbenoids possessed inhibitory activity against LPS-induced NO production [4], which was further confirmed by this study.…”
Section: Resultsmentioning
confidence: 99%
“…This led us to obtain three new compounds, 1-(4 0 -hydroxybenzyl)-imbricatin (1), (E)-4 0 -hydroxy-2 0 ,3,3 0 , 5-tetramethoxystilbene (2), and (E)-3,4 0 -dihydroxy-2,6-bis(4-hydroxybenzyl)-2 0 ,3 0 ,5-trimethoxystilbene (3), together with 15 known stilbene derivatives, imbricatin (4) [9], phoyunnanin C (5) [5], eulophiol (6) [10], 2,5-dihydroxy-3,4-dimethoxy-9,10-dihydrophenanthrene (7) [11], lusianthridin (8) [12], 2,5-dihydroxy-3, 4,6-trimethoxy-9,10-dihydrophenanthrene (9) [13], 2,4,7-trihydroxy-9,10-dihydrophenanthrene (10) [14], coelonin (11) [15], bulbophyllanthrin (12) [16], moscatin (13) [17], 2,5-dihydroxy-3,4-dimethoxyphenanthrene (14) [9], phoyunbene B (15) [4], (E)-2 0 ,3-dihydroxy-2,6-bis(4-hydroxybenzyl)-5-methoxystilbene (16) [18], bulbocol (17) [19], and 3,3 0 -dihydroxy-2,6-bis(4-hydroxybenzyl)-5-methoxybibenzyl (18) [20] ( Figure 1). Compound 1 was isolated as yellow crystal and its molecular formula C 23 H 20 O 5 was analyzed by HR-EI-MS at m/z 514.1987 [M] -.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacology: Antioxidant activity reported. [63][64][65] Phytochemistry: Stilbenoids reported Pharmacology: Antioxidant activity reported.…”
Section: -62mentioning
confidence: 99%